2022
DOI: 10.3390/ma15093306
|View full text |Cite
|
Sign up to set email alerts
|

Material and Structural Functionalization of Knitted Fabrics for Sportswear

Abstract: Comfort is an important quality criterion, especially for sportswear. It influences well-being, performance and efficiency. The necessary dissipation of heat and air flow, at high metabolic rates, must be designed and planned in advance. The influence of structure, density, mass and thickness of fabric were considered as well as yarn material composition, yarn linear density, yarn evenness and yarn hairiness. The influence of the mentioned parameters on thermal properties and air permeability was calculated. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Therefore, the moisture management behavior of textiles depends on the concentration of the coating or softener, the type, the chemical nature and other parameters applied in the finishing process. 20,23,24 The air permeability property of fabrics depends on fiber content, [25][26][27][28] fiber shape, fiber fineness, yarn manufacturing method, 21 linear density, fabric structure, such as length and density, tightness factor, yarn or fabric treatment, 6 the fiber surface area and yarn density. 5,29 For example, looser or with lower density Finecool ® and Airclo ® polyester yarns have higher air permeability than denser Coolmax ® polyester yarns with grooves along the length of the fiber surface.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the moisture management behavior of textiles depends on the concentration of the coating or softener, the type, the chemical nature and other parameters applied in the finishing process. 20,23,24 The air permeability property of fabrics depends on fiber content, [25][26][27][28] fiber shape, fiber fineness, yarn manufacturing method, 21 linear density, fabric structure, such as length and density, tightness factor, yarn or fabric treatment, 6 the fiber surface area and yarn density. 5,29 For example, looser or with lower density Finecool ® and Airclo ® polyester yarns have higher air permeability than denser Coolmax ® polyester yarns with grooves along the length of the fiber surface.…”
Section: Introductionmentioning
confidence: 99%
“…The air permeability of fabrics increases due to a reduction in hairiness and air gaps in the yarn. 27,28 Antibacterial polyester fabrics treated with sodium hydroxide and casein have higher air permeability than fabric treated with casein due to the filling of air gaps in knitted fabrics. 30 Analysis of the literature on moisture management and air permeability of textiles has shown that these properties of the investigated fabrics depend on many factors, but among the investigated textiles, none were manufactured by applying 1×1 rib and half-Milano knit patterns using different percentages of fiber mixture of cotton/antistatic polyester yarns and finally treated with an antibacterial finish.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Most of the current research related to the thermal and humid comfort of clothing has focused on the types of fabrics 24,25 and the lightweight design of synthetic materials. 26,27 To carry out exercise training and human body recovery in an effective way, 28 there are also a few studies that use cooling schemes to cool down. 29,30 The research on improving the comfort of sportswear and having a positive impact on sports efficiency by optimizing style structure and improving fabric performance is not mentioned.…”
mentioning
confidence: 99%
“…Bragov et al [ 2 ] emphasized that comfort is an important quality criterion, especially for sportswear. The authors offered a statistically significant model of multiple linear regression equations to predict the thermal comfort of knitted fabric.…”
mentioning
confidence: 99%